2013 IEEE/ASME International Conference on Advanced Intelligent Mechatronics 2013
DOI: 10.1109/aim.2013.6584231
|View full text |Cite
|
Sign up to set email alerts
|

Brain controlled robotic exoskeleton for neurorehabilitation

Abstract: Robots have been used for decades to enhance productivity, reliability and accuracy for repetitive tasks. More recently robot capabilities have been exploited in medical rehabilitation applications for this same reason. While robots can provide consistent physical therapy there is limited evidence that robot assisted physical therapy has any improved outcomes over human administered therapy. Patient participation is the most important factor for rehabilitating the neural system after injury or stroke and so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The user's brain activity is measured using electrodes, amplified and analyzed to determine the mode of operation [37][38][39]. Among the different brain signal recording methods, currently electroencephalography (EEG) is predominantly used since it is non-invasive and therefore 3 Block diagram of the proposed classification of the control strategies subparts.…”
Section: Brain-computer Interface (Bci)mentioning
confidence: 99%
“…The user's brain activity is measured using electrodes, amplified and analyzed to determine the mode of operation [37][38][39]. Among the different brain signal recording methods, currently electroencephalography (EEG) is predominantly used since it is non-invasive and therefore 3 Block diagram of the proposed classification of the control strategies subparts.…”
Section: Brain-computer Interface (Bci)mentioning
confidence: 99%
“…When considering studies in the context of lower-limb rehabilitation, some other papers are available. Using an SSVEP paradigm, it was shown that a lower limb exoskeleton could be controlled by both a step by step approach and in a continuous way [ 174 ]. In [ 175 ], a walk rehabilitation system that recognizes five types of intention is proposed and an 80% accuracy is claimed.…”
Section: Development Of Non-invasive Brain-computer Interfaces Dedicamentioning
confidence: 99%
“…Among the promising techniques is a brain-computer interface (BCI) by which electroencephalogram (EEG) signals (i.e., surface electrical brain activity measured on multiple electrodes placed on the scalp) are typically used to operate the rehabilitation device. Such a device provides visual stimulation that evokes brain activity of event-related potentials (ERP) [5,6] or steady-state visually evoked potentials (SSVEP), which correspond to the temporal frequency of the stimulus [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For actual rehabilitation purposes, the time allocated to feature extraction should be short, possibly with completion in hours. Existing learning algorithms [5][6][7][8] usually take several weeks to months for machine learning calculations to extract characteristic EEG patterns from a specific frequency range.…”
Section: Introductionmentioning
confidence: 99%